2018
DOI: 10.3390/su10051495
|View full text |Cite
|
Sign up to set email alerts
|

Work Integration of the Roma: Between Family and Labor Market

Abstract: The social inclusion of the Roma population represents a topical issue that must be considered from both the scientific and social action perspectives. Governments, through their pivotal role in defining societal values and norms, are essential to promoting the social inclusion of vulnerable populations. To argue this perspective, the present study examines some other pivotal social institutions that play relevant roles in the professional insertion of the Roma: family, education, and the residential community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Further, distinctive panel data analysis on two panels, EU-15 (old EU MS) and EU-13 (new MS), revealed that constant policy rethinking, adequate strategies, measures and tools for the active ageing population support become outlier keystones that entail a successful integration of the older people within all life dimensions, in order to counteract the multiple effects on social and economic conditions (Neţoiu & Cârstina, 2014;Pânzaru, 2015), following the good practice model of the Nordic States (Hall & Gylfi, 2014). A special attention must be given to redesign the labour market policies within the EU-13, since these countries are facing numerous shortcomings as high total unemployment rates of various ethnic groups and youths neither in employment nor in education (Marcu et al, 2015;Marcu & Dobrota, 2016;Dincă & Lucheș, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further, distinctive panel data analysis on two panels, EU-15 (old EU MS) and EU-13 (new MS), revealed that constant policy rethinking, adequate strategies, measures and tools for the active ageing population support become outlier keystones that entail a successful integration of the older people within all life dimensions, in order to counteract the multiple effects on social and economic conditions (Neţoiu & Cârstina, 2014;Pânzaru, 2015), following the good practice model of the Nordic States (Hall & Gylfi, 2014). A special attention must be given to redesign the labour market policies within the EU-13, since these countries are facing numerous shortcomings as high total unemployment rates of various ethnic groups and youths neither in employment nor in education (Marcu et al, 2015;Marcu & Dobrota, 2016;Dincă & Lucheș, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A particular attention shall be paid to enhance other observed and unobserved managerial attributes and firm characteristics (other proxies) that determine executive compensation incentives and firm financial performance following the research of Coles and Li [84]. Last but not least, other areas that will employ our attention are the management features in different ethnic groups [85], and the further impact on firm competitiveness [86,87], will both be augmented in our future research. Acknowledgments: The authors are indebted to two anonymous referees for their accurate and very constructive comments that were extremely useful in framing the overall research.…”
Section: Discussionmentioning
confidence: 99%
“…Active labour market programmes (ALMPs) are themselves based on preserving good working habits by integrating the unemployed into work rather than providing passive income support [20], so a positive impact is expected. However, services such as monitoring and counselling post-employment are almost non-existent, which might lead to critical gaps in Roma workforce development [21]. The monitoring of the work trajectories of segregated Roma and other hard-to-employ groups seem to be important in order to determine whether improved working habits really do increase employability in a way that is sustainable on the labour market.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of education was seen by informants as another crucial outcome that increases employability and through this improves health. The relationship between education and unemployment has been extensively substantiated [21,22,23], as has that between education and health [24,25]. Roma are significantly less educated than non-Roma [26], and the employment gap of Roma has been shown to be strongly related to their low education [21,26].…”
Section: Discussionmentioning
confidence: 99%